Improving Science Learning Outcomes Using Inquiry Based Learning Contextual Learning Models in Class V SDN Paku Alam Banjar Regency - Mahrita; M. Ihsan Ramadhani; Saidahtunnoor (Journal of Sustainable Development Science, 2022)
The objectives of this study are: 1) to find out how the activities of teachers in implementing the Inquiry based learning learning model at SDN Paku Alam, Banjar Regency, and 2) Knowing how the students' learning outcomes in science follow using the Inquiry based learning learning model at SDN Paku Alam, Banjar Regency. The subjects in this study were all students at SDN Paku Alam, Banjar Regency. The sampling technique used was purposive sampling totaling 12 students of class V. The data mining tool used was a test. Data analysis used indicators of success: 1) Teacher activity reaches a good category if it reaches 71 and 2) Students' science learning outcomes are said to be good if mastery reaches 80% of the number of students. Based on data analysis, it is concluded 1) the use of Inquiry based learning in class V at SDN Paku Alam, Banjar Regency, cycle I was in the good category with a percentage of 84.21% and increased in the second cycle to 89.47% in the very good category, and 2) The results of learning science class V at SDN Paku Alam, Banjar Regency, cycle I. 65% and increased in the second cycle to 84.16%.